Photorespiration Coupled With CO2 Assimilation Protects Photosystem I From Photoinhibition Under Moderate Poly(Ethylene Glycol)-Induced Osmotic Stress in Rice - Wada, Shinya; Miyake, Chikahiro; Makino, Amane; Suzuki, Yuji (Frontiers in Plant Science, 2020)
Photorespiration coupled with CO2 assimilation is thought to act as a defense system against photoinhibition caused by drought stress. In the present study, we examined whether such a mechanism is operative for the protection of photosystem I (PSI) in rice (Oryza sativa L.) including transgenic plants with decreased and increased Rubisco content (RBCS-antisense and RBCS-sense plants, respectively). All plants were hydroponically grown and drought stress was imposed using hydroponic culture solutions containing poly(ethylene glycol) (PEG) at 16% or 20% (w/v) for two days. In wild-type plants, the rates of CO2 assimilation (A) were significantly decreased by the PEG treatment, whereas the photorespiration activity estimated from the rates of electron transport in photosystem II (PSII) and A were not affected. The maximal quantum efficiency of PSII (Fv/Fm) and the maximal activity of PSI (Pm) were also not affected. In RBCS-antisense plants, A and the estimated photorespiration activity were considerably lower than those in wild-type plants in the presence or absence of the PEG treatment. Pm and both Fv/Fm and Pm decreased in the 16% PEG-treated and 20% PEG-treated RBCS-antisense plants, respectively. Thus, the decrease in Rubisco content led to the photoinhibition of PSI and PSII, indicating the importance of photorespiration coupled with CO2 assimilation for the protection of PSI from drought stress. It was also shown that PSI was more sensitive to drought stress than PSII. In the PEG-treated wild-type and RBCS-antisense plants, drought-stress responses of the photosynthetic electron transport reactions upstream of PSI led to the oxidation of P700, which is thought to prevent PSI from over-reduction. Although such a defense system operated, it was not sufficient for the protection of PSI in RBCS-antisense plants. In addition, there were no large differences in the parameters measured between wild-type and RBCS-sense plants, as overproduction of Rubisco did not increase photorespiration activity.